ASSESSMENT METHODS AND TREATMENT OF ODONTOGENIC PHLEGMONS IN CHILDREN: CLINICAL FEATURES AND MANAGEMENT - Akhmedov Ilhom Ibrahimovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract Odontogenic phlegmon is a serious purulent infection of the maxillofacial region that originates from dental sources. In pediatric patients, the clinical course, diagnosis, and treatment require special attention due to the anatomical and immunological features of children. This paper discusses the clinical presentation, diagnostic approaches, and therapeutic strategies for managing odontogenic phlegmon in children.